Mirror Mechanism Behind Visual–Auditory Interaction: Evidence From Event-Related Potentials in Children With Cochlear Implants - Wang, Junbo; Liu, Jiahao; Lai, Kaiyin; Zhang, Qi; Zheng, Yiqing; Wang, Suiping; Liang, Maojin (Frontiers in Neuroscience, 2021)
The mechanism underlying visual-induced auditory interaction is still under discussion. Here, we provide evidence that the mirror mechanism underlies visual–auditory interactions. In this study, visual stimuli were divided into two major groups—mirror stimuli that were able to activate mirror neurons and non-mirror stimuli that were not able to activate mirror neurons. The two groups were further divided into six subgroups as follows: visual speech-related mirror stimuli, visual speech-irrelevant mirror stimuli, and non-mirror stimuli with four different luminance levels. Participants were 25 children with cochlear implants (CIs) who underwent an event-related potential (ERP) and speech recognition task. The main results were as follows: (1) there were significant differences in P1, N1, and P2 ERPs between mirror stimuli and non-mirror stimuli; (2) these ERP differences between mirror and non-mirror stimuli were partly driven by Brodmann areas 41 and 42 in the superior temporal gyrus; (3) ERP component differences between visual speech-related mirror and non-mirror stimuli were partly driven by Brodmann area 39 (visual speech area), which was not observed when comparing the visual speech-irrelevant stimulus and non-mirror groups; and (4) ERPs evoked by visual speech-related mirror stimuli had more components correlated with speech recognition than ERPs evoked by non-mirror stimuli, while ERPs evoked by speech-irrelevant mirror stimuli were not significantly different to those induced by the non-mirror stimuli. These results indicate the following: (1) mirror and non-mirror stimuli differ in their associated neural activation; (2) the visual–auditory interaction possibly led to ERP differences, as Brodmann areas 41 and 42 constitute the primary auditory cortex; (3) mirror neurons could be responsible for the ERP differences, considering that Brodmann area 39 is associated with processing information about speech-related mirror stimuli; and (4) ERPs evoked by visual speech-related mirror stimuli could better reflect speech recognition ability. These results support the hypothesis that a mirror mechanism underlies visual–auditory interactions.